1991
DOI: 10.1042/bj2760541
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and characterization of N-acetylneuraminate lyase from Escherichia coli

Abstract: N-Acetylneuraminate lyase produced by Escherichia coli was purified and crystallized from a genetically engineered strain (E. coli SF8/pNAL1). The enzyme showed apparent molecular masses of 105,000 Da on gel filtration and 35,000 Da on SDS/PAGE, suggesting that the enzyme is a trimer. The apparent optimum pH and temperature were found to be 6.5-7.0 and 80 degrees C respectively. The Km values for N-acetylneuraminate and N-glycollylneuraminate were 3.3 and 3.3 mM respectively. The enzyme was inhibited by reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
5
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 26 publications
(14 reference statements)
12
60
5
1
Order By: Relevance
“…In contrast, GiCLO particles were the most sensitive to heat treatment but showed resistance to extremes of pH. This is consistent with previous research on the soluble form of these enzymes (10,(25)(26)(27)(28)(29)(30). Native soluble BLA has been shown to be stable up to 75°C and between pH 6.0 and 8.5 (29).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, GiCLO particles were the most sensitive to heat treatment but showed resistance to extremes of pH. This is consistent with previous research on the soluble form of these enzymes (10,(25)(26)(27)(28)(29)(30). Native soluble BLA has been shown to be stable up to 75°C and between pH 6.0 and 8.5 (29).…”
Section: Discussionsupporting
confidence: 80%
“…No structural or stability data are currently available for OpdA from A. radiobacter; however, other similar phosphotriesterases have been shown to be stable up to 50°C and between pH 6.0 and 10.0 (31,32). The isoelectric points of BLA and NanA are 6.9 and 4.5, respectively (27,29), while the isoelectric point of a well-characterized homologous phosphotriesterase from Brevundimonas diminuta is 8.3 (33). Therefore, OpdA is proposed to be more stable at alkaline pH.…”
Section: Discussionmentioning
confidence: 97%
“…However, the original study using the E. coli deletion strains indicated that the nature of the C-5 amino substituent in Sia does not affect transport or degradation (60). The aldolases from C. perfringens and E. coli are capable of cleaving a range of neuraminic acid derivatives with different substituents at C-5, including formyl, succinyl, and glycolyl neuraminic acids (1,48). Regarding the NanT permease, it has been established that many bacteria, both gram negative and gram positive, exhibit an active proton symporter-type mechanism (59).…”
Section: Resultsmentioning
confidence: 99%
“…Aldolase cleavage was determined both spectrophotometrically and chromatographically (HPLC). The first method measured the decrease in absorbance at 340 nm corresponding to the oxidation of NADH produced by lactate dehydrogenase (LDH) when pyruvate appeared as a consequence of the hydrolysis of Neu5Ac into such compound and of ManNAc produced by LpNAL (1,43). The standard reaction medium (1 ml) for the above-described assay, which was carried out in a Shimadzu UV-2401 PC spectrophotometer, contained 150 M NADH, 0.5 U LDH, 10 mM Neu5Ac, and 1.5 g of purified LpNAL in 20 mM phosphate buffer (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%